A novel MAC protocol for power line communication with integrated NFC for smart home applications - G. Haridoss; J. Arun Pandian; K. Sivaranjani; L. Thanga Mariappan (Scientific Reports)
Abstract Our day-to-day lives have become comfortable and sophisticated with many recent technologies. Likewise, today’s world has been enhanced by new innovative technologies. Everyone is moving towards smart cities and smart homes. Power-Line Communication (PLC) is a breakthrough communication technology that supports cost-effectiveness with maximum speed and reliable communication performance, producing no interference complications for wireless signal transmission. It operates over existing power line cables, avoiding other transmission mediums by using low-cost PLC chipsets. Transmission between two cities is performed using power grid technology. However, with a PLC chipset, data transmission is managed locally within towns and inside homes. To avoid inconveniences such as noise, significant signal reduction, and time period fluctuations, a novel Medium Access Control (MAC) protocol is proposed to improve the stability of the PLC network and data transmission efficiency. Using a Modified Intra-cluster MAC algorithm based on time allocation to enhance the reliability of access nodes in the PLC network is a novel attempt. Moreover, this work ensures enhancements in data transmission speed and security. Finally, the security-enhanced PLC network is integrated with Near Field Communication (NFC) technology for intelligent home applications.